Phlēng patiphāk : watthanatham dontrī læ phāpsath̨̄on sangkhom kh̨̄ong chāo Tambon Khao Th̨̄ong, ʻAmph̄œ Phayuhakhīrī, Čhangwat Nakh̨̄on Sawan - Kritsanā S̄ængth̨ōng, 1966- (Sūn Sinlapawatthanatham, Sathāban Rātchaphat Nakh̨̄on Sawan, 1997)
Chiefly text and study on social and culture reflections in folk songs of Phayuhakhiri District, Nakhon Sawan Province, Thailand.